EMPOWERING WITH LANGUAGE Communicative English for Undergraduate Learners - CENGAGE (Delhi Cengage Learning India Pvt Ltd, 2025)
The Cengage textbook Empowering with Language is a comprehensive textbook-cum-workbook primarily designed for undergraduate students to develop essential language skills for effective communication.
Communication Skills
Communication
Keywords: Communication; English